Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0343
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Control and Fruit Development

Abstract: The sections in this article are Introduction Fruit Development: A Matter of Cell Number and Cell Size Cell Cycle Gene Expression and Fruit Development Altering the Cell Cycle towards Endoreduplication: A Key Feature for Fruit Growth Genetic Control of Fruit Size Metabolic Control of Fruit Development and Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Here, we supposed that MCM 2, 3, 4, and 7 might upregulate the expression of photosynthetic genes and indirectly regulate photosynthesis substance allocation and transportation by modulating DNA replication or endoreduplication. Our findings were consistent with those of previous studies, which reported that the parenchymal cells that store starch, sugar, and other substances in the fruits or seeds of plants reproduce through DNA replication or endoreduplication [44]. In order to verify the MCM expression mode in strawberry buds, we selected MCM2 as an identified protein and found that it shows a significantly high expression in RLB when compared with DSB and ASB (Fig.…”
Section: Tmt Revealed the Heterogeneity Of Stolon Buds In Strawberrysupporting
confidence: 91%
“…Here, we supposed that MCM 2, 3, 4, and 7 might upregulate the expression of photosynthetic genes and indirectly regulate photosynthesis substance allocation and transportation by modulating DNA replication or endoreduplication. Our findings were consistent with those of previous studies, which reported that the parenchymal cells that store starch, sugar, and other substances in the fruits or seeds of plants reproduce through DNA replication or endoreduplication [44]. In order to verify the MCM expression mode in strawberry buds, we selected MCM2 as an identified protein and found that it shows a significantly high expression in RLB when compared with DSB and ASB (Fig.…”
Section: Tmt Revealed the Heterogeneity Of Stolon Buds In Strawberrysupporting
confidence: 91%
“…Our current data showed that some of the measured parameters do not respond to AM inoculation (PW, CI), and others were highly responsive (FFW, PT, MD), while the seed number (SN) only responded to the fertilization level, as expected. Interestingly, all of the parameters that were specifically modulated by mycorrhizal status, fruit diameter, weight, and pericarp thickness had a strong correlation with fruit growth, rather than fruit ripening [51,52] suggesting that fruit development and not only ripening is probably deeply impacted by mycorrhization. Additionally, fruit shape and size traits (such as FFW, PT and MD) have been linked to the turgor of parenchyma cells, which is closely related to cell wall features [25,53].…”
Section: Resultsmentioning
confidence: 99%
“…The earliest phase of fruit set is characterized by a period of intense mitotic activity and involves the generation of positive signals that drive the re-activation of cell cycle-related genes (Azzi et al, 2015). MADS-box genes could function as integrators of the ovary development signal triggered by fertilization (Chevalier, 2007) since they are induced immediately after anthesis in the ovary walls (Busi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%